Non-twist flax fibre reinforcement of lightweight plywood - Marcus Cordier; Ole Gonnsen; Carsten Mai (Discover Applied Sciences)
Abstract Using lignin-phenol-formaldehyde (LPF) impregnated flax fibres is a little-studied method for reinforcing plywood through natural materials with only a modest increase in density. The main objective of this study was to assess the effects on the mechanical properties of small-leaved lime (Tilia cordata) veneer-based lightweight plywood (density <600 $$\,kg\,m^{-3}$$ ) by inserting non-twist flax fibre fabrics pre-impregnated with lignin-phenol-formaldehyde resin. Two types of composite materials were compared—fully impregnated flax fibre fabric (‘Fullpreg’) and pre-impregnated flax fibre fabric (‘Prepreg’) inserted beneath the top layers of five-layered plywood boards. A 5-layered plywood without insertions served as a reference. Plywoods with insertions of pre-impregnated flax fibre fabrics (81.7 $$N\,mm^{-2}$$ ) exhibited up to 9.4% higher modulus of rupture (MOR) compared to the reference (74.7 $$N\,mm^{-2}$$ ), while fully impregnated insertions (83.9 $$N\,mm^{-2}$$ ) achieved 12.3% higher MOR than the reference in the grain direction of the top layers. Simultaneously, the modulus of elasticity (MOE) decreased for both variants due to the insertion, with reductions of 5.7% parallel and 10.3% perpendicular to grain direction. The surface soundness was 1.56 $$N\,mm^{-2}$$ for the ‘Fullpreg’ variant and 1.47 $$N\,mm^{-2}$$ for the ’Prepreg’ variant, compared to 1.25 $$N\,mm^{-2}$$ for the ’Reference’ variant. The mean thickness swelling was 8.7% for the ‘Fullpreg’ variant and 8.8% for the ‘Prepreg’ variant, while the mean water uptake was 23.9% for both variants, compared to the reference of 22.2%. Considering the resulting properties, the insertion of LPF pre-impregnated flax fibre fabrics can be an appropriate technique for improving the properties of plywood using natural materials.